Guardiani del Nord. Gli Stati Uniti e la geopolitica della crisi climatica nell'Artico - Lavorio, Agata (Milano University Press, 2023)
Can climate change really shape United States geography and geopolitics in the Arctic? So far, the question has seldom been raised. This essay demonstrates how the climate crisis is undermining traditional geopolitical concepts, such as the northern invulnerability of the American continent and the very concept of insularity of the United States, while climate change influences - but not determines - national security and defense policies. The research is dedicated to International Relations scholars, but can be appreciated also by readers coming from different fields, interested in politics, geopolitics, and climate change.